2005
DOI: 10.1061/(asce)0733-9445(2005)131:4(589)
|View full text |Cite
|
Sign up to set email alerts
|

Direct Estimation of Seismic Demand and Capacity of Multidegree-of-Freedom Systems through Incremental Dynamic Analysis of Single Degree of Freedom Approximation

Abstract: Introducing a fast and accurate method to estimate the seismic demand and capacity of first-mode dominated multi-degree-of-freedom (MDOF) systems by approximating the Incremental Dynamic Analysis (IDA) through the Static Pushover (SPO) analysis. While the computer-intensive IDA would require several nonlinear dynamic analyses under multiple suitably-scaled ground motion records, the simpler SPO helps approximate the MDOF system with a single-degree-of-freedom (SDOF) oscillator whose backbone matches the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(141 citation statements)
references
References 13 publications
1
136
1
3
Order By: Relevance
“…Several proposals are available in the literature for the determination of an approximate IDA curve starting from nonlinear static analysis, e.g. (Vamvatsikos and Cornell 2005;Dolsek and Fajfar 2005;Han and Chopra 2006). The latter, based on the modal pushover analysis (MPA) technique (Chopra and Goel 2002), has been chosen here due to its easy implementation with commercial analysis packages, since it uses invariant force patterns, and its applicability to general spatial geometries (Reyes and Chopra 2011).…”
Section: Methods B and Response Analysis Via Modal Pushovermentioning
confidence: 99%
“…Several proposals are available in the literature for the determination of an approximate IDA curve starting from nonlinear static analysis, e.g. (Vamvatsikos and Cornell 2005;Dolsek and Fajfar 2005;Han and Chopra 2006). The latter, based on the modal pushover analysis (MPA) technique (Chopra and Goel 2002), has been chosen here due to its easy implementation with commercial analysis packages, since it uses invariant force patterns, and its applicability to general spatial geometries (Reyes and Chopra 2011).…”
Section: Methods B and Response Analysis Via Modal Pushovermentioning
confidence: 99%
“…2). These conversions entail passage from nondimensional coordinates R -μ to spectral acceleration -roof drift format, the possibility of adding the response variability at the nominal yield point that the MDOF system experiences due to the effect of higher modes (but is lost on its SDOF counterpart, [13]) and possibly a roof drift to inter-storey drift conversion, since the latter is oftentimes better suited for the definition of limit-state thresholds.…”
Section: Sdof To Mdof Conversion Of the Fractile Ida Curvesmentioning
confidence: 99%
“…It can be observed that the adherence of the approximate SPO2FRAG result to its analytical counterpart is equally good for both cases of RDR and IDR, where the 50% and 84% fractile IDAs are concerned, but less so for the 16% curve. One of the reasons behind this is the fact that the shape of the SPO employed in this example (first-mode proportional lateral load profile) was able to capture one of the more unfavorable failure mechanisms (see also [13]). A comparison between the fragility functions resulting as SPO2FRAG output and those calculated by means of IDA can be found in Fig.…”
Section: Spo2frag Vs Idamentioning
confidence: 99%
“…Several researchers evaluated the collapse capacity of structures by use of simplified SDOF models, because of their efficacy in terms of calculation time. Certainly, the results can be extended to the Multi-Degree-of-Freedom (MDOF) structures [17,18]. The P-Δ effects are moments that are created in the structure by gravity loads due to displacement by the lateral force.…”
Section: Introductionmentioning
confidence: 99%